Fetal Ovarian Cyst—A Scoping Review of the Data from the Last 10 Years - Carmen Bucuri; Dan Mihu; Andrei Malutan; Valentin Oprea; Costin Berceanu; Ionel Nati; Maria Rada; Cristina Ormindean; Ligia Blaga; Razvan Ciortea (Medicina, 2023)
Abdominal cystic masses are diagnosed during the intrauterine period and have a relatively low incidence. Fetal ovarian cysts are the most common form diagnosed prenatally or immediately after birth. The pathophysiology of the development of these types of tumors is not fully elucidated, with ovarian hyperstimulation caused by maternal and placental hormones being the most accepted hypothesis. During intrauterine development, the diagnosis of fetal ovarian cysts is most often made accidentally during usual check-up ultrasounds corresponding to the first, second, and third trimesters of pregnancy. We conducted a scoping review with the aim to map the current knowledge regarding the treatment of fetal ovarian cysts diagnosed in the intrauterine period. Focusing on the articles published in the last 10 years in the specialized literature, we tried to identify a conceptualization regarding the surveillance and treatment of these anomalies.